Habitat characteristics of Anopheles spp. larvae: Potential malaria vectors in the coastal areas of Gaura Village, West Sumba: Karakteristik habitat larva Anopheles spp.: Vektor potensial malaria pantai di Desa Gaura, Sumba Barat - Muhammad Muzhaffar Daud; Justus Edyson Tangkuyah; Edo Yungki Saputra; Martini Martini; Retno Hestiningsih; Fauzi Muh (Perhimpunan Entomologi Indonesia, 2026)
Malaria remains a public health burden in tropical coastal regions, where complex environmental conditions support vector populations and increase transmission risk, particularly among vulnerable groups. Understanding the environmental characteristics of Anopheles spp. breeding habitats is essential for explaining vector distribution and informing control strategies. This study analyzed the environmental characteristics of potential Anopheles spp. breeding habitats in the coastal areas of Gaura Village. An observational descriptive survey with a cross-sectional approach was conducted using purposive spatial sampling across two survey rounds, measuring physical, chemical, and biological variables. A total of 12 breeding sites were identified, with confirmed vectors including Anopheles sundaicus (Rodenwaldt), An. subpictus Grassi, and An. barbirostris van der Wulp. Larval densities peaked in confined anthropogenic microhabitats, particularly buffalo wallows (3.5 larvae/dip) and footprints (3.1 larvae/dip). The habitats exhibited wide physicochemical variability (temperature 29.0–39.4°C; pH 7.3–9.2; salinity 0–20‰). Principal component analysis (PCA) explained 61.3% of total variation, distinguishing habitats along two gradients: PC1 (34.3%), driven by structural area, dissolved oxygen, and light intensity; and PC2 (27.0%), driven by pH and salinity. All highly productive habitats were located within 512 meters of residential areas, placing communities within the active flight range of vectors. These findings indicate that malaria transmission risk in coastal Gaura Village is driven by environmentally diverse yet spatially clustered larval habitats, particularly small, human-proximal sites associated with livestock, highlighting the need for targeted larval source management.